2021
DOI: 10.1038/s41598-021-95803-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of L-shaped heat source and magnetic field on heat transfer and irreversibilities in nanofluid-filled oblique complex enclosure

Abstract: In this paper, the natural convection heat transfer of water/alumina nanofluid is investigated in a closed square cavity. An oblique magnetic field is applied on the cavity of angle $$\gamma$$ γ . There is also radiation heat transfer in the cavity. The cavity includes a high-temperature source of L-shape. A low-temperature source as a quadrant of a circle is placed at the corner of the cavity. All other walls are well insulated. The novelty of this work is a low-temperature o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Alnaqi et al (2020) studied the natural convection and entropy generation in a cubical cavity and observed that total entropy fairly increased with an increase in Rayleigh number until a certain value, when it then rose significantly. Similar studies have also been carried out (Bondareva et al, 2017;Hussein et al, 2016;Yang et al, 2021;Zhang et al, 2021;Ishak et al, 2021;Oztop et al, 2017). Natural convection in Saltbox roof is analysed for a hot climate region, with the aim of helping designers improve the thermal comfort in such conditions.…”
Section: Introductionmentioning
confidence: 81%
“…Alnaqi et al (2020) studied the natural convection and entropy generation in a cubical cavity and observed that total entropy fairly increased with an increase in Rayleigh number until a certain value, when it then rose significantly. Similar studies have also been carried out (Bondareva et al, 2017;Hussein et al, 2016;Yang et al, 2021;Zhang et al, 2021;Ishak et al, 2021;Oztop et al, 2017). Natural convection in Saltbox roof is analysed for a hot climate region, with the aim of helping designers improve the thermal comfort in such conditions.…”
Section: Introductionmentioning
confidence: 81%
“…In a study on Casson fluid flow due to double-diffusive natural convection in staggered cavities, Hussain et al [ 14 ] discovered that when entropy creation is significant, the overall entropy output increases with increasing the Casson number. Zhang et al [ 15 ] explored a cavity with a high-temperature L-shaped source using Fortran code based on the control volume approach and a simple algorithm. The smallest value of the Bejan number was found at a magnetic field of 15°.…”
Section: Background Informationmentioning
confidence: 99%
“…Several examinations have taken into account the influence of an external magnetic field in recent times (Mansour et al. , 2019; Moolya and Satheesh, 2020; Zhang et al. , 2021; El-Shorbagy et al.…”
Section: Introductionmentioning
confidence: 99%
“…Iftikhar et al (2023) examined how MHD affects convective flow and heat transfer characteristics in a U-shaped cavity containing both water and ferrofluid. Several examinations have taken into account the influence of an external magnetic field in recent times (Mansour et al, 2019; Entropy generation Moolya and Satheesh, 2020;Zhang et al, 2021;El-Shorbagy et al, 2021;Algehyne et al, 2023).…”
Section: Introductionmentioning
confidence: 99%